Molecular Beam Scattering Experiments as a Sensitive Probe of the Interaction in Bromine–Noble Gas Complexes - Cappelletti, David; Cinti, Antonio; Nicoziani, Andrea; Falcinelli, Stefano; Pirani, Fernando (Frontiers in Chemistry, 2019)
This paper reports for the first time molecular beam experiments for the scattering of He, Ne, and Ar by the Br2 molecule, with the aim of probing in detail the intermolecular interaction. Measurements have been performed under the experimental condition to resolve the glory pattern, a quantum interference effect observable in the collision velocity dependence of the integral cross section. We analyzed the experimental data with a reliable potential model defined as a combination of an anisotropic van der Waals component with the additional contribution due to charge transfer and polar flattening effects related to the formation of an intermolecular halogen bond. The model involves few parameters, whose values are related to fundamental physical properties of the interacting partners and it allows an internally consistent comparison of the stability of the gas phase adducts formed by Br2 moiety with different noble gases as well as homologous complexes with the Cl2 molecule. The same model appears to be also easily generalized to describe the interaction of diatomic halogen molecules in the excited B(3Π) electronic state where the halogen bond contribution tends to vanish and a more anisotropic van der Waals components dominate the structure of the complexes with noble gases.